Metabolic Syndrome and Clinical Outcomes of Patients with Gastric Cancer: A Meta-Analysis - Huang, Zhiyang; Zhou, Jianwei; Chen, Long; Zhang, Yibing (Hormone and Metabolic Research, 2023)
Metabolic syndrome (MetS) is suggested to participate in the pathogenesis and progress of some cancers via inducing low-grade systemic inflammation. However, the influence of MetS on patients with gastric cancer (GC) remains not fully determined. A systematic review and meta-analysis was therefore performed to evaluate the influence of MetS on clinical outcomes of patients with GC. A search of PubMed, Embase, Web of Science, Wanfang, and CNKI retrieved relevant cohort studies from the inception of the databases to October 11, 2022. We pooled the results using a random-effects model that incorporates heterogeneity. In the meta-analysis, 6649 patients with GC were included, and all of them received gastrectomy. A total of 1248 (18.8%) patients had MetS at baseline. Pooled results showed that MetS was associated with higher risks of postoperative complications [risk ratio (RR): 2.41, 95% confidence interval (CI): 1.85 to 3.14, p<0.001; I2=55%], overall mortality (RR: 1.73, 95% CI: 1.85 to 3.14, p<0.001; I2=77%), and recurrence of GC (RR: 2.00, 95% CI: 1.10 to 3.63, p=0.02; I2=39%). Subgroup analyses showed similar results in prospective and retrospective cohort studies and in studies with MetS diagnosed with the Chinese Diabetes Society criteria and the National Cholesterol Education Program Adult Treatment Panel III criteria (p for subgroup difference all>0.05). In patients with GC after gastrectomy, MetS may be a predictor of high incidence of postoperative complications, cancer recurrence, and overall mortality.
Keywords: metabolic syndrome; gastric cancer; gastrectomy; clinical outcomes; meta-analysis